Path following of underactuated vehicles via integral line of sight guidance and fixed‐time heading control. Issue 1 (23rd March 2022) - Zhang, Pengfei; Chen, Qiyuan; He, Ping
Abstract: This study investigates the integral line of sight (ILOS) path‐following control problem of surface vehicles whose dynamics feature external disturbances, model uncertainties, and actuator dead zones. First, introducing the ILOS guidance law, the path‐following control problem is converted to stabilising a 2nd order nonlinear system. Subsequently, the fixed‐time observer is designed to estimate and compensate for the uncertainties and unknown external disturbances while overcoming the actuator dead zones. Finally, the trajectory tracking control strategy is designed based on the fixed‐time observer. Numerical examples are given to illustrate the effectiveness of the proposed approaches.